2021
DOI: 10.20463/pan.2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of royal jelly protein on bone mineral density and strength in ovariectomized female rats

Abstract: [Purpose] Sex hormones deficiency leads to dramatically bone loss in particular postmenopausal women. Royal jelly has anti-osteoporosis effect due to maintain bone volume in that condition. We hypothesized that royal jelly protein (RJP, a latent residue after extracting royal jelly) also prevents bone deficient in ovariectomized (OVX) female rats, the animal model of postmenopausal women. [Methods] Female Sprague-Dawley rats (n = 30, 6 weeks age old) were sham operated (Sham; sham operated group, n = 7), OVX c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The calcium and phosphate levels in bone tissue were also higher in RJ and bee pollen groups, suggesting that both RJ and bee pollen could be beneficial in clinical practice. Hatori et al obtained similar results [221]. They studied the effects of royal jelly protein (RJP) on the bone mineral density and strength in ovariectomized Sprague-Dawley rats that received RJ for 8 weeks.…”
Section: Royal Jelly and Osteoporosismentioning
confidence: 77%
“…The calcium and phosphate levels in bone tissue were also higher in RJ and bee pollen groups, suggesting that both RJ and bee pollen could be beneficial in clinical practice. Hatori et al obtained similar results [221]. They studied the effects of royal jelly protein (RJP) on the bone mineral density and strength in ovariectomized Sprague-Dawley rats that received RJ for 8 weeks.…”
Section: Royal Jelly and Osteoporosismentioning
confidence: 77%
“…Researchers have demonstrated rapid expansion and regeneration of maxillary bone in rats and believe that the antioxidative action of royal jelly ( Özan et al, 2015 ), along with its ability to induce TGF-β, may be the mechanisms through which this compound exerts its effects on bone tissue ( Koya-Miyata et al, 2002 ; Koya-Miyata et al, 2004 ). Assessments have revealed that royal jelly can inhibit the decline in bone mineral density and strength resulting from hormone deficiency in ovariectomized rat models ( Hattori and Omi, 2021 ), and it can even reverse osteoporosis induced by glucocorticoids. These studies need to include molecular assays in the future.…”
Section: Royal Jellymentioning
confidence: 99%
“…Moreover, insect proteins contain specific amino acid sequences and domains that can interact with cell surface receptors and activate intracellular signaling pathways involved in bone formation [ 114 ]. These proteins, such as royal jelly proteins, can stimulate the expression of osteogenic markers and induce the differentiation of mesenchymal stem cells into osteoblasts, which are responsible for bone synthesis [ 115 ]. However, despite their potential, the use of insect proteins in bone tissue engineering is still in its early stages, and further research is needed to explore their full capabilities.…”
Section: Cell Unit-inspired Building Blocks For Bone/cartilage Regene...mentioning
confidence: 99%